Festival, antenne del contemporaneo: Una giornata di riflessione tra studiosi e operatori della danza in Italia - Acca, Fabio (Mimesis Journal, 2024)
On May 24, 2019, as part of the Festival Interplay, a day of reflection was organized in Turin, with the title Festival, antennas of the contemporary. The event was attended by a large amount of cultural operators and artistic directors who have been promoting contemporary dance in Italy for years. The article summarizes and contextualizes the main points of the discussion, with a proactive approach that takes into account both theoretical and more directly technical suggestions, with the idea that the trace of thought deposited can be not only a testimony and a deepening on the key issues of the event but also a collection of good practices to be put in place, in the joint effort to share what can be considered a collective heritage, developed here in the manner of a story partly turned to the past, but in part, and above all, turned to the future.